Huronia's Double Bind: How Institutionalisation Bears Out on the Body. (April 2021) - Rinaldi, Jen; Rossiter, Kate
Abstract : Frequently missing from histories of forced institutionalisation are close readings of the enduring impact on survivors' corporeality. In this article the authors analyse interview data featuring people who survived the Huronia Regional Centre: a total institution designed to warehouse people with intellectual disabilities that operated in Canada from 1876 to 2009. These interviews reveal the impact of institutional technologies on the bodies of the institutionalised, and how institutional survivors resisted those technologies. Institutional rituals meant to organise and cleanse residents, resulted in the reification of institutional subjects as inescapably contaminated. Drawing from Mary Douglas's theory of dirt and Julia Kristeva's interpretation of dirt as abjection, the authors engage with interview data on daily institutional care routines, particularly dressing, eating, showering, and the administration of medication, to show how these rituals produced for the institutionalised subject meanings around gender and disability as markers of defilement. The authors argue that the kinds of deeply oppressive and often violent rituals central to lived experiences of institutionalisation are grounded in the assumption that disabled gendered bodies are already-abject, hence the institutional demand for the institutionalised to be brought under control.